Minute ventilation/carbon dioxide production in chronic heart failure - Piergiuseppe Agostoni (European Respiratory Review, 2021)
In chronic heart failure, minute ventilation (V′E) for a given carbon dioxide production (V′CO2) might be abnormally high during exercise due to increased dead space ventilation, lung stiffness, chemo- and metaboreflex sensitivity, early metabolic acidosis and abnormal pulmonary haemodynamics. The V′E versus V′CO2 relationship, analysed either as ratio or as slope, enables us to evaluate the causes and entity of the V′E/perfusion mismatch. Moreover, the V′E axis intercept, i.e. when V′CO2 is extrapolated to 0, embeds information on exercise-induced dead space changes, while the analysis of end-tidal and arterial CO2 pressures provides knowledge about reflex activities. The V′E versus V′CO2 relationship has a relevant prognostic power either alone or, better, when included within prognostic scores. The V′E versus V′CO2 slope is reported as an absolute number with a recognised cut-off prognostic value of 35, except for specific diseases such as hypertrophic cardiomyopathy and idiopathic cardiomyopathy, where a lower cut-off has been suggested. However, nowadays, it is more appropriate to report V′E versus V′CO2 slope as percentage of the predicted value, due to age and gender interferences. Relevant attention is needed in V′E versus V′CO2 analysis in the presence of heart failure comorbidities. Finally, V′E versus V′CO2 abnormalities are relevant targets for treatment in heart failure.